EBC for improving tgo and silicon-based bond coat

CN122648937APending Publication Date: 2026-08-28GENERAL ELECTRIC CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610234749.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-02-28
Filing Date
2026-02-27
Publication Date
2026-08-28

Smart Images

  • Figure CN122648937A_ABST
    Figure CN122648937A_ABST
Patent Text Reader

Abstract

A coated component and a method of forming the same are provided. The coated component includes a silicon-containing substrate having a surface, a bond coat on the surface of the silicon-containing substrate, and an environmental barrier coating on the bond coat. The bond coat includes a silicon-based matrix having a dispersion of reinforcing phase therein. Upon oxidation of the bond coat, a TGO layer is formed, the TGO layer including a dispersion of alumino-silicate based crystals in a silicate-based oxide matrix.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure generally relates to environmental barrier coatings for coated components and methods for forming the same. Background Technology

[0002] Silicon-based materials are used in high-temperature components of gas turbine engines, such as airfoils (e.g., blades, rotor blades), combustor liners, and shrouds. Silicon-based materials can include silicon-based monolithic ceramic materials, intermetallic materials, and composite materials. For example, silicon-based ceramic matrix composites (CMCs) can include silicon-containing fibers reinforcing a silicon-containing matrix phase. Summary of the Invention

[0003] A first aspect of the present invention provides a coating component, comprising:

[0004] A silicon-containing substrate with a surface;

[0005] An adhesive coating on the surface of the silicon-containing substrate, wherein the adhesive coating comprises a silicon matrix in which a reinforcing phase is dispersed; and

[0006] An environmental barrier coating on the adhesive coating.

[0007] A second aspect of the present invention provides a method for forming a coated component, the method comprising:

[0008] An adhesive coating is formed on the surface of a silicon-containing substrate, wherein the adhesive coating comprises a silicon substrate in which a reinforcing phase is dispersed; and

[0009] An environmental barrier coating is formed on the adhesive coating; wherein, when the coated component is subsequently exposed to an oxidizing environment, a thermally grown oxide layer is formed between the adhesive coating and the environmental barrier coating, and on the adhesive coating, wherein the thermally grown oxide layer comprises a dispersion of aluminosilicate-based crystals in a silicate-based oxide matrix. Attached Figure Description

[0010] The complete and implementable disclosure (including its best mode) of this disclosure is set forth in the specification with reference to the accompanying drawings, wherein:

[0011] Figure 1 This is a schematic cross-sectional view of an exemplary coated component, which includes: a silicon-containing substrate coated with an adhesive coating and an environmental barrier coating;

[0012] Figure 2 This is a cross-sectional schematic diagram of an exemplary coated component, which includes: a silicon-containing substrate coated with an adhesive coating, a thermally grown oxide layer on the adhesive coating, and an environmental barrier coating;

[0013] Figure 3 This is a schematic diagram of the exemplary method for forming a coated component described herein.

[0014] definition

[0015] The word "exemplary" is used herein to mean "serving as an example, instance, or illustration." Any specific implementation described herein as "exemplary" is not necessarily to be construed as preferred or advantageous over other specific implementations. Furthermore, unless otherwise expressly stated, all embodiments described herein should be considered exemplary.

[0016] Unless the context clearly indicates otherwise, the singular forms “a,” “an,” and “the” include plural references.

[0017] In cases such as “at least one of A, B and C”, the term “at least one of…” means only A, only B, only C, or any combination of A, B and C.

[0018] As used herein, the terms “first,” “second,” and “third” are used interchangeably to distinguish one component from another and are not intended to indicate the location or importance of the individual components.

[0019] Chemical elements are discussed in this disclosure using their common chemical abbreviations, such as those commonly found in the periodic table. For example, hydrogen is represented by its common chemical abbreviation H; helium by its common chemical abbreviation He; and so on. As used herein, “RE” refers to rare earth elements or mixtures of rare earth elements. More specifically, “RE” refers to the rare earth elements or mixtures of the following: scandium (Sc), yttrium (Y), lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), and lutetium (Lu).

[0020] As used herein, “silicon dioxide” refers to silicon oxide in the form of SiO2. Conversely, “elemental silicon” refers to silicon that is free of any alloying material except for unavoidable impurities. In the art, it is sometimes referred to as “metal silicon.” Elemental silicon has a melting point of approximately 1414°C.

[0021] As used in this article, “aluminum oxide” refers to aluminum oxide in the form of Al2O3.

[0022] As used herein, the term "mullite" generally refers to a mineral containing both alumina and silica (i.e., an aluminosilicate). That is, mullite is a chemical compound of alumina and silica. Typically, the ratio of alumina (Al₂O₃) to silica (SiO₂) in mullite can be about 3:2 (e.g., in the range of 10 mol% for alumina / silica of 3:2). However, a ratio of about 2:1 has also been reported in mullite (e.g., in the range of 10 mol% for alumina / silica of 2:1).

[0023] As used herein, the term "boromullite" generally refers to a mineral containing aluminum, boron, silicon, and oxygen (i.e., an aluminosilicate). That is, boromullite is a chemical compound of aluminum oxide, boron oxide, and silicon dioxide. In some embodiments, the chemical formula of boromullite may be in the range of 10 mol% for an aluminum oxide / boron oxide ratio of 9:2. For example, boromullite may be in the range of 10 mol% for a combination of Al₂SiO₅ and Al₅BO₉ to form Al₉BSi₂O₅. 19 A mixture within the range of 10 mol%.

[0024] As used herein, the term "borosilicate glass" generally refers to glass in which silicon dioxide and boron trioxide are the main glass-forming components.

[0025] In this disclosure, when layers are described as being “on” or “above” another layer or substrate, it should be understood that, unless explicitly stated otherwise, these layers may be in direct contact with each other or have another layer or feature between them. Therefore, these terms simply describe the relative positions of the layers to each other and do not necessarily mean “above”, as the relative position above or below depends on the orientation of the device to the observer. Detailed Implementation

[0026] Reference will now be made in detail to the present embodiments of this disclosure, one or more of which are illustrated in the accompanying drawings. Detailed descriptions use numbers and letters to denote features in the drawings. The same or similar reference numerals in the drawings and description are used to denote the same or similar portions of this disclosure.

[0027] Silicon carbide and silicon nitride ceramics oxidize in dry, high-temperature environments. This oxidation produces a passivated silicon oxide scale on the material's surface. In humid, high-temperature environments containing water vapor (such as turbine engines), both oxidation and thinning occur due to the formation of the passivated silicon oxide scale and the subsequent conversion of the silicon oxide into gaseous silicon hydroxide. To prevent thinning in humid, high-temperature environments, an environmental barrier coating (EBC) is deposited on the silicon carbide and silicon nitride materials.

[0028] Currently, EBC materials are made of rare-earth silicate compounds. These materials isolate water vapor, preventing it from reaching the silicon oxide scale on the silicon carbide or silicon nitride surface, thus preventing thinning. However, this material cannot prevent oxygen permeation, which leads to oxidation of the underlying substrate. Substrate oxidation produces a passivated silicon oxide scale, accompanied by the release of carbon- or nitrogen-containing oxide gases. Carbon-containing (i.e., CO, CO2) or nitrogen-containing (i.e., NO, NO2, etc.) oxide gases cannot escape through the dense EBC, thus forming bubbles, which can cause EBC peeling. To date, the use of silicon binder coatings has become a solution to this blistering problem. Silicon binder coatings form a thermally grown oxide (TGO) layer of silicon dioxide under the EBC without releasing gaseous byproducts.

[0029] However, pure silica has a strong tendency to devitrify or crystallize. Crystalline silica is prone to cracking due to phase transitions, thus threatening the mechanical integrity of EBCs. Therefore, there is an urgent need in the art for an improved TGO layer.

[0030] A coated component and a method for forming the same are generally provided. The coated component has a binder coating configured to form an improved TGO layer between the binder coating and the EBC (Extracorporeal Chamber). Typically, the binder coating comprises a silicon-based matrix and a reinforcing phase, which, upon oxidation during use of the coated component, forms a TGO layer comprising a dispersion of aluminosilicate-based crystals in a silicate-based oxide matrix. Without being bound by any particular theory, it is believed that aluminosilicate-based crystals (e.g., mullite-based materials) can form crystals in a silicate-based oxide matrix (e.g., borosilicate glass), which can contribute to enhancing the creep resistance of the TGO layer. Therefore, the resulting TGO layer can exhibit stronger resistance to crystallization and higher creep strength than pure silica. Consequently, the TGO layer in the EBC can remain amorphous for a longer period, effectively extending the lifetime of the EBC system. The TGO layer is typically formed from components in the binder coating, as explained in more detail below.

[0031] Reference Figure 1 An exemplary coated component 10 is shown, comprising a silicon-containing substrate 12 having a surface 14 on which an EBC system 15 is disposed. The EBC system 15 includes an adhesive coating 16 on the surface 14 of the silicon-containing substrate 12 and an EBC 18 on the adhesive coating 16. Typically, the adhesive coating 16 may be used between the substrate 12 and the EBC 18 to enhance the adhesion of the EBC 18 to the substrate 12 and potentially serve as a sacrificial oxide layer within the EBC system 15.

[0032] Typically, the adhesive coating 16 comprises a silicon-based matrix in which a reinforcing phase is dispersed. (Refer to...) Figure 1The binder coating 16 typically includes a variety of base phases, such as a silicon-based matrix 26 (e.g., boron-doped silicon or elemental silicon) and a reinforcing phase 28 dispersed therein (e.g., containing aluminosilicates, such as mullite, boron mullite, or mixtures thereof). In some embodiments, the binder coating may include 75 wt% to 99.9 wt% of the silicon-based matrix 26 and 0.1 wt% to 25 wt% of the reinforcing phase 28.

[0033] Either or both of the silicon matrix 26 and / or the reinforcing phase 28 contain boron (e.g., in boron-doped silicon or boron mullite) so that borosilicate glass can be formed in the subsequent TGO layer. Figure 2 ).

[0034] In one embodiment, the silicon substrate 26 comprises boron-doped silicon, and the reinforcing phase 28 comprises a mullite-based material (e.g., mullite). For example, the binder coating 16 may be at least 50 wt% of the boron-doped silicon as the silicon substrate 26 (e.g., 50 wt% to 95 wt% boron-doped silicon). Such boron-doped silicon may comprise 0.1 wt% to 10 wt% boron and 90 wt% to 99.9 wt% silicon (i.e., elemental silicon), for example 0.1 wt% to 5 wt% boron and 95 wt% to 99.9 wt% silicon. Without wishing to be bound by any particular theory, it is believed that oxidation of such a binder coating 16 will form a TGO layer 20 (…). Figure 2 The TGO layer comprises borosilicate glass oxidized from borosilicate silicon. As the TGO layer 20 grows and the binder coating 16 is consumed upon exposure to oxygen, the mullite-based material in the binder coating 16 can form a portion of the TGO layer 20, which can undergo a dissolution-reprecipitation process within the borosilicate glass and change shape. The mullite-based material can also react with the borosilicate glass and alter its composition.

[0035] In another embodiment, the binder coating 16 may comprise a silicon-based substrate 26 (containing silicon, e.g., elemental silicon or boron-doped silicon) and a reinforcing phase 28 (containing boron mullite). For example, the binder coating 16 may be at least 50 wt% silicon as the silicon-based substrate 26 (e.g., 50 wt% to 95 wt% silicon). Since boron is present in the boron mullite, the silicon in the binder coating 16 may be in the form of elemental silicon. Without wishing to be bound by any particular theory, it is believed that oxidation of such a binder coating 16 would form a TGO layer 20 comprising a borosilicate glass formed by the co-oxidation of silicon and boron mullite. Mullite-based material may migrate from the binder coating 16 into the TGO layer 20, wherein it crystallizes within the borosilicate glass.

[0036] Typically, mullite exhibits a relatively slow oxygen diffusion rate at all temperatures of interest (even up to approximately 1650°C (e.g., 1200°C to 1650°C)). Above 1200°C, the only other crystalline oxide believed to have a lower oxygen diffusion rate than mullite is alumina, which has a very high coefficient of thermal expansion relative to substrate 12, making it impossible to deposit a dense coating without exfoliation. While the coefficient of thermal expansion (“CTE”) of mullite is similar to that of SiC-based CMC substrates and silicon (silicon-based substrate 26), the CTE of mullite does not perfectly match that of SiC or Si. For example, the CTE of mullite is approximately 5.5 × 10⁻⁶. -6 / K, while the CTE of boron mullite is approximately 4.9 × 10⁻⁶. -6 / K. Both mullite and boron mullite have good compatibility with silicon and CMC, thus contributing to the mechanical stability of the adhesive coating 16.

[0037] However, if the binder coating 16 is too thick, this slight mismatch in CTE can lead to problems related to thermal expansion, such as cracking and / or delamination. For example, a binder coating 16 with a thickness of 508 µm is believed to cause problems related to CTE mismatch after repeated exposure to operating temperatures. On the other hand, a binder coating 16 with a maximum thickness of less than 381 µm (e.g., 25.4 µm to 381 µm) is believed to withstand such operating temperatures better without significant problems caused by CTE mismatch. In one specific embodiment, the maximum thickness of the binder coating 16 is 254 µm, for example, from 75 µm to 254 µm. In certain embodiments, the multiple phases of the binder coating 16 have substantially the same thickness. For example, a silicon-based phase may have a first thickness, and a mullite-based phase may have a second thickness, wherein the first thickness is within 5% of the second thickness.

[0038] Reference Figure 2 The binder coating 16 includes silicon and components configured to form a TGO layer 20 upon oxidation of the binder coating 16. The TGO layer 20 comprises a dispersion of aluminosilicate-based crystals (e.g., mullite-based materials) in a silicate-based oxide matrix (e.g., borosilicate glass). The TGO layer 20 is typically formed on the binder coating 16, located between the binder coating 16 and the EBC 18.

[0039] As previously described, TGO layer 20 comprises a silicate-based oxide matrix (e.g., borosilicate glass) and aluminosilicate-based crystals (e.g., mullite-based materials). Silica may also be present in TGO layer 20, which can be formed during silicon oxidation in the binder coating 16. Without wishing to be bound by any particular theory, it is believed that the dispersion of aluminosilicate-based crystals (e.g., mullite-based materials) is present in sufficient quantity to substantially stabilize the amorphous structure of TGO layer 20, particularly the amorphous structure of the silicate-based oxide matrix (e.g., borosilicate glass) in TGO layer 20. Therefore, TGO layer 20 is more resistant to high-temperature creep compared to borosilicate glass TGO layers that do not contain a dispersion of aluminosilicate-based crystals (e.g., mullite-based materials). By maintaining its amorphous state, the silicate-based oxide matrix (e.g., borosilicate glass) in TGO layer 20 helps to prevent cracking during thermal cycling. Without being bound by any particular theory, it is believed that if the TGO layer 20 is crystalline, it will take the form of cristobalite and undergo a reversible phase transition at approximately 270°C. This phase transition may involve volume changes, which could lead to cracking of the TGO layer 20.

[0040] In one embodiment, the TGO layer 20 comprises 75 wt% to 99.9 wt% of a silicate-based oxide matrix (e.g., borosilicate glass). In another embodiment, the TGO layer 20 comprises 0.1 wt% to 25 wt% of aluminosilicate-based crystals (e.g., mullite-based materials). Without wishing to be bound by any particular theory, it is believed that an excess of aluminosilicate-based crystals in the TGO layer 20 may lead to phase separation, as the aluminosilicate-based crystals may form a mullite-rich phase (which crystallizes), while the silicate-based oxide matrix remains amorphous.

[0041] Typically, aluminosilicate-based crystals provide mechanical stability within the TGO layer 20. (Refer to...) Figure 2 The TGO layer 20 shows aluminosilicate-based crystals 22 dispersed within the silicate-based oxide matrix 24. In some embodiments, at least a portion of the aluminosilicate-based crystals 22 spans the TGO layer 20. Therefore, this portion of the aluminosilicate-based crystals 22 spanning the TGO layer 20 can interact with (e.g., bond to) the adhesive coating 16 and the overlying EBC 18, thereby providing mechanical stability therebetween. In some embodiments, at least a portion of the aluminosilicate-based crystals 22 interlock with each other within the TGO layer 20. Therefore, the aluminosilicate-based crystals 22 can form an interlocking network spanning the TGO layer 20, thereby providing mechanical connection between the adhesive coating 16 and the overlying EBC 18.

[0042] In some embodiments, the aluminosilicate-based crystal 22 may be elongated in nature, for example, having an aspect ratio greater than 5. For example, the aspect ratio of the aluminosilicate-based crystal 22 may be 10-1000.

[0043] The aluminosilicate-based crystal 22 may comprise a mullite-based material, such as mullite, boron mullite, or both (e.g., mixtures thereof). The specific composition of the mullite-based material in the aluminosilicate-based crystal 22 within the TGO layer 20 can be controlled according to the composition of the adhesive coating 16, which forms the TGO layer 20 upon oxidation during use of the coated component. That is, when the coated component is exposed to an oxidizing environment, the adhesive coating 16 may cause the migration and oxidation of the TGO-forming components, thereby forming borosilicate glass in situ from the components of the adhesive coating 16 and migrating the mullite-based material therein from the adhesive coating 16.

[0044] In some implementations... Figure 1 and Figure 2 The substrate 12 is formed of a silicon-containing material (e.g., a ceramic matrix composite (“CMC”)). As used herein, a ceramic matrix composite or “CMC” refers to a class of materials that include reinforcing materials (e.g., reinforcing fibers) surrounded by a ceramic matrix phase. Typically, the reinforcing fibers provide structural integrity to the ceramic matrix. Some examples of matrix materials for CMCs may include, but are not limited to, non-oxide silicon-based materials (e.g., silicon carbide, silicon nitride, or mixtures thereof), oxide ceramics (e.g., silicon oxycarbide, silicon oxynitride, aluminum oxide (Al₂O₃), silicon dioxide (SiO₂), aluminosilicates, or mixtures thereof), or mixtures thereof. Optionally, ceramic particles (e.g., oxides of Si, Al, Zr, Y, and combinations thereof) and inorganic fillers (e.g., pyrophyllite, wollastonite, mica, talc, kyanite, and montmorillonite) may also be included within the CMC matrix.

[0045] Some examples of reinforcing fibers for CMC may include, but are not limited to, non-oxide silicon-based materials (e.g., silicon carbide, silicon nitride, or mixtures thereof), non-oxide carbon-based materials (e.g., carbon), oxide ceramics (e.g., silicon oxycarbonate, silicon oxynitride, aluminum oxide (Al2O3), silicon dioxide (SiO2), aluminosilicates such as mullite, or mixtures thereof), or mixtures thereof.

[0046] Typically, a particular CMC can be referred to as a combination of its fiber type / matrix type. For example, carbon fiber reinforced silicon carbide is C / SiC; silicon carbide fiber reinforced silicon carbide is SiC / SiC; silicon carbide fiber reinforced silicon nitride is SiC / SiN; silicon carbide fiber reinforced silicon carbide / silicon nitride matrix mixture is SiC / SiC-SiN, and so on. In other examples, a CMC may include a matrix and reinforcing fibers, the reinforcing fibers comprising oxide-based materials such as aluminum oxide (Al₂O₃), silicon dioxide (SiO₂), aluminosilicates, and mixtures thereof. Aluminosilicates may include crystalline materials such as mullite (3Al₂O₃·2SiO₂), and glassy aluminosilicates.

[0047] In some embodiments, the reinforcing fibers may be bundled and / or coated before being contained in the matrix. For example, the fiber bundles may be formed as reinforcing tapes, such as unidirectional reinforcing tapes. Multiple tapes may be stacked together to form a preformed part. The fiber bundles may be impregnated with a slurry composition before or after the formation of the preform. The preform may then undergo heat treatment (e.g., curing or burn-out) to produce a high coke residue in the preform, followed by a chemical treatment (e.g., infiltration with a silicon melt) to obtain a part formed from a CMC material having the desired chemical composition.

[0048] These materials, along with certain monolithic ceramics (i.e., ceramic materials without reinforcement), are particularly well-suited for higher-temperature applications. Furthermore, these ceramic materials are lighter than high-temperature alloys, yet still provide strength and durability for components made from them. Therefore, the use of such materials in numerous gas turbine components used in the higher-temperature range of gas turbine engines—such as airfoils (e.g., turbines and blades), combustors, shields, and other similar components—is currently being considered. These components would benefit from the lighter weight and higher-temperature capabilities that these materials can offer.

[0049] As described above, the adhesive coating 16 and the TGO layer 20 can be used in conjunction with the EBC 18 to form a coated component 10 for the EBC system 15 with improved effective lifespan. As used herein, an environmental barrier coating or “EBC” refers to a coating comprising one or more layers of ceramic material, each layer providing specific or multifunctional protection to the underlying CMC. An EBC typically comprises multiple layers, such as rare earth silicate coatings (e.g., rare earth disilicates, such as yttrium ytterbium disilicate (YbYDS) deposited by slurry or air plasma spraying (“APS deposition”), alkaline earth aluminosilicates (e.g., coatings comprising barium-strontium-aluminum silicates (BSAS) with a composition range covering BaO, SrO, Al2O3, SiO2, or combinations thereof), sealing layers (e.g., rare earth disilicates), outer coatings (e.g., rare earth monosilicates, such as yttrium monosilicate (YMS) deposited by slurry or APS deposition), or combinations thereof. One or more layers may be doped as needed, and the EBC may also be coated with an abrasion-resistant coating.

[0050] EBC 18 may comprise one or more layers of any combination of materials selected from the chemical composition of a typical EBC 18 or thermal barrier coating (“TBC”) layer, including but not limited to rare earth silicates (e.g., monosilicates and disilicates), aluminosilicates (e.g., mullite, barium strontium aluminum silicate (BSAS), rare earth aluminum silicates, etc.), hafnium oxide, zirconium oxide, stabilized hafnium oxide, stabilized zirconium oxide, rare earth hafnium salts, rare earth zirconates, rare earth gallium oxide, etc. EBC 18 may comprise a hafnium oxide layer, an aluminum oxide layer, or both. Alternatively or additionally, EBC 18 may comprise a rare earth disilicate layer, a rare earth monosilicate layer, or both. EBC 18 may be formed from a plurality of separate layers 19. In the illustrated embodiment, EBC 18 may comprise a sealing layer, a silicate layer, or any combination of the aforementioned layers.

[0051] The coated component 10 is particularly suitable for use as components in high-temperature environments, such as components present in gas turbine engines, including combustor components, turbine blades, shrouds, nozzles, heat shields, and wheel blades. Specifically, the coated component 10 can be a CMC component located within the hot gas flow path of the gas turbine, allowing the EBC system to form an environmental barrier for the underlying substrate 12 to protect components within the gas turbine when exposed to the hot gas flow path. Furthermore, the coated component 10 is particularly suitable for rotating components subjected to prolonged use under strong centrifugal forces.

[0052] In general, methods for forming coated parts (such as any of the exemplary coated parts described above) are also provided. (See reference...) Figure 3An exemplary method 30 for forming a coated component (such as the coated component described above) is shown. At 32, an adhesive coating is formed on the surface of a substrate (e.g., a silicon-containing substrate), wherein the adhesive coating comprises a silicon-based matrix in which a reinforcing phase is dispersed. At 34, an EBC is formed on the adhesive coating. At 36, the coated component is optionally exposed to an oxidizing environment, such that a TGO is formed on the adhesive coating between the adhesive coating and the environmental barrier coating, as described above.

[0053] Other aspects are provided by the subject of the following clauses:

[0054] A coated component includes: a silicon-containing substrate having a surface; an adhesive coating on the surface of the silicon-containing substrate, wherein the adhesive coating includes a silicon-based matrix in which a reinforcing phase is dispersed; and an environmental barrier coating on the adhesive coating.

[0055] The coated component according to any one of the foregoing clauses, wherein the reinforcing phase comprises aluminosilicate.

[0056] The coated component according to any one of the foregoing clauses, wherein the aluminosilicate includes mullite or boron mullite.

[0057] In any of the preceding clauses, the coated component is wherein the silicon in the adhesive coating is boron-doped silicon.

[0058] The coated component according to any one of the foregoing clauses, wherein the adhesive coating comprises 50wt%-95wt% boron-doped silicon.

[0059] The coated component according to any one of the foregoing clauses, wherein the boron-doped silicon comprises 0.1wt%-10wt% boron and 90wt%-99.9wt% silicon.

[0060] The coated component according to any one of the foregoing clauses, wherein the reinforcing phase comprises mullite.

[0061] The coated component according to any one of the foregoing clauses, wherein the adhesive coating comprises elemental silicon.

[0062] The coated component according to any one of the foregoing clauses, wherein the reinforcing phase comprises boron mullite.

[0063] The coated component according to any one of the foregoing clauses, wherein the boron mullite has a chemical formula in the range of 10 mol% of alumina / boron oxide at a ratio of 9:2.

[0064] The coated component according to any one of the foregoing clauses, wherein the adhesive coating comprises 0.1wt%-25wt% boron mullite.

[0065] The coating component according to any one of the foregoing clauses further includes: a thermally grown oxide layer located between the adhesive coating and the environmental barrier coating, wherein the thermally grown oxide layer comprises a dispersion of aluminosilicate-based crystals in a silicate-based oxide matrix.

[0066] The coating component according to any one of the foregoing clauses, wherein the thermally grown oxide comprises a dispersion of 0.1wt%-25wt% aluminosilicate-based crystals and 75wt%-99.9wt% silicate-based oxide matrix.

[0067] The coated component according to any one of the foregoing clauses, wherein the aluminosilicate-based crystal comprises a mullite-based material.

[0068] The coated component according to any one of the foregoing clauses, wherein the silicate-based oxide matrix comprises borosilicate glass.

[0069] The coated component according to any one of the foregoing clauses, wherein at least a portion of the aluminosilicate-based crystals spans the thermally grown oxide layer.

[0070] In any of the preceding clauses, the coated component contains aluminum silicate-based crystals interlocked within a thermally grown oxide layer.

[0071] The coated component according to any one of the foregoing clauses, wherein the aspect ratio of the aluminosilicate-based crystal is greater than 5.

[0072] The coated component according to any one of the foregoing clauses, wherein the substrate is a ceramic matrix composite material.

[0073] A gas turbine engine includes a coated component as described in any of the preceding clauses, wherein the environmental barrier coating of the coated component is exposed to a hot gas passage within the gas turbine engine.

[0074] A method for forming a coated component as described in any of the preceding clauses.

[0075] A method for forming a coated component, the method comprising: forming an adhesive coating on a surface of a silicon-containing substrate, wherein the adhesive coating comprises a silicon-based matrix in which a reinforcing phase is dispersed; and forming an environmental barrier coating on the adhesive coating; wherein, when the coated component is subsequently exposed to an oxidizing environment, a thermally grown oxide layer is formed on the adhesive coating between the adhesive coating and the environmental barrier coating, wherein the thermally grown oxide layer comprises a dispersion of aluminosilicate-based crystals in a silicate-based oxide matrix.

[0076] This written description uses examples to disclose this disclosure (including the best mode) and also enables any person skilled in the art to implement this disclosure, including making and using any apparatus or system and performing any combination of methods. The pursuable scope of this disclosure is defined by the claims and may include other examples that would occur to a person skilled in the art. Such other examples are intended to fall within the scope of the claims if they include structural elements that are not indistinguishable from the literal language of the claims, or if they include equivalent structural elements that are not substantially indistinguishable from the literal language of the claims.

Claims

1. A coated component, comprising: A silicon-containing substrate with a surface; An adhesive coating on the surface of the silicon-containing substrate, wherein the adhesive coating comprises a silicon-based matrix in which a reinforcing phase is dispersed; as well as An environmental barrier coating on the adhesive coating.

2. The coated component according to claim 1, wherein, The reinforcing phase comprises aluminosilicate.

3. The coated component according to claim 2, wherein, The aluminosilicate includes mullite or boron mullite.

4. The coated component according to claim 1, wherein, The silicon in the adhesive coating is boron-doped silicon.

5. The coated component according to claim 4, wherein, The adhesive coating contains 50wt%-95wt% boron-doped silicon.

6. The coated component according to claim 4, wherein, The boron-doped silicon comprises 0.1wt%-10wt% boron and 90wt%-99.9wt% silicon.

7. The coated component according to claim 4, wherein, The reinforcing phase comprises mullite.

8. The coated component according to claim 1, wherein, The adhesive coating contains elemental silicon.

9. The coated component according to claim 8, wherein, The reinforcing phase comprises boron mullite.

10. The coated component according to claim 9, wherein, Boron mullite has a chemical formula in the range of 10 mol% with an aluminum oxide / boron oxide ratio of 9:2.